ChemInform Abstract: Anthradifuran, a Furan Analogue of Pentacene, and Its Isomers, Exhibiting Solid‐State Photoluminescence. Issue 7 (22nd February 2013) - Tsuji, Hayato; Shoyama, Kazutaka; Nakamura, Eiichi
Abstract Synthesis, structure, and photophysical properties of the linearly fused anthra[2, 3‐b:6, 7‐b′]difuran (II), and its zigzag‐shaped isomers (III) and (IV) are described.